Escrituras del Raj: el vaivén indológico entre el romanticismo y el orientalismo - Muñoz, Adrián (El Colegio de México, 2026)
Since the seminal work of both Ray mond Schwab and Edward Said, several scholars have noted the important relationship that took place between Orientalism and Imperialism. This paper seeks to redress these dynamics by especia lly focusing on the complex, epistemic shapings that framed the British orientalist project since the 18th century and its interplay with English Romanticism. By revisiting the literary work of some British authors, the aim is to reexamine the various perceptions, receptions, and adaptations of Indian lore in the Romantic imagery; finally, I will briefly discuss some of the civilizational implications of the imperialist project. Thus, the article will identify the different approaches toward India by British authors (around and in the aftermath of English Romanticism), showing that they were far from sharing a common prejudice.